Enhanced direct ethanol production by cofactor optimization of cell surface‐displayed xylose isomerase in yeast. (26th April 2017) - Sasaki, Yusuke; Takagi, Toshiyuki; Motone, Keisuke; Kuroda, Kouichi; Ueda, Mitsuyoshi
Abstract : Xylose isomerase (XylC) from Clostridium cellulovorans can simultaneously perform isomerization and fermentation ofd ‐xylose, the main component of lignocellulosic biomass, and is an attractive candidate enzyme. In this study, we optimized a specified metal cation in a previously established Saccharomyces cerevisiae strain displaying XylC. We investigated the effect of each metal cation on the catalytic function of the XylC‐displaying S. cerevisiae. Results showed that the divalent cobalt cations (Co 2+ ) especially enhanced the activity by 46‐fold. Co 2+ also contributed tod ‐xylose fermentation, which resulted in improving ethanol yields and xylose consumption rates by 6.0‐ and 2.7‐fold, respectively. Utility of the extracellular xylose isomerization system was exhibited in the presence of mixed sugar. XylC‐displaying yeast showed the fasterd ‐xylose uptake than the yeast producing XI intracellularly. Furthermore, direct xylan saccharification and fermentation was performed by unique yeast co‐culture system. A xylan‐degrading yeast strain was established by displaying two kinds of xylanases; endo‐1, 4‐β‐xylanase (Xyn11B) from Saccharophagus degradans, and β‐xylosidase (XlnD) from Aspergillus niger. The yeast co‐culture system enabled fine‐tuning of the initial ratios of the displayed enzymes (Xyn11B:XlnD:XylC) by adjusting the inoculation ratios of Xylanases (Xyn11B and XlnD)‐displaying yeast and XylC‐displaying yeast. When the enzymes were inoculated at the ratio of 1:1:2 (1.39 × 10 13 : 1.39 × 10 13 : 2.78 × 10 13 molecules), 6.0 g/L ethanol was produced from xylan. Thus, the cofactor optimization and the yeast co‐culture system developed in this study could expand the prospect of biofuels production from lignocellulosic biomass. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1068–1076, 2017